Analysing phenotypic variation in barn swallows (Hirundo rustica) across China to assess subspecies status. (22nd August 2020) - Liu, Yu; Scordato, Elizabeth S C; Zhang, Zhengwang; Evans, Matthew; Safran, Rebecca J
Abstract: Phenotypic variation is often used to delineate species and subspecies boundaries. Statistical analysis of phenotypic variation within a species is helpful both for understanding biodiversity and for its conservation. At least three named subspecies of barn swallows ( Hirundo rustica ) have distributions that span China, yet, to date, no systematic study of phenotypic differentiation has been applied to understand the delineation of these subspecies. In this study, we collected 510 samples of barn swallow from 23 populations in China, including two recognized subspecies, H. r. rustica and H. r. gutturalis, and one potential subspecies, H. r. mandschurica . With these samples, we examined and found morphometric and colour differences among different populations. Western Chinese barn swallows ( H. r. rustica ) have larger body size and could be clearly differentiated from eastern H. r. gutturalis and H. r. mandschurica, while north-eastern populations (named H. r. mandschurica ) have darker, redder ventral plumage than H. r. rustica and H. r. gutturalis . However, we inferred that although there were phenotypic differences between H. r. mandschurica and H. r. gutturalis, they were not sufficiently distinct to assign them to separate subspecies based on the 75% rule for defining subspecies.